The Import Competence of a Peroxisomal Membrane Protein Is Determined by Pex19p before the Docking Step - Pinto, Manuel P.; Grou, Cláudia P.; Alencastre, Inês S.; Oliveira, Márcia E.; Sá-Miranda, Clara; Fransen, Marc; Azevedo, Jorge E. (The Journal of biological chemistry, 2006)
Biogenesis of the mammalian peroxisomal membrane requires the action of Pex3p and Pex16p, two proteins present in the organelle membrane, and Pex19p, a protein that displays a dual subcellular distribution (peroxisomal and cytosolic). Pex19p interacts with most peroxisomal intrinsic membrane proteins, but whether this property reflects its role as an import receptor for this class of proteins or a chaperone-like function in the assembly/disassembly of peroxisomal membrane proteins has been the subject of much controversy. Here, we describe an in vitro system particularly suited to address this issue. It is shown that insertion of a reporter protein into the peroxisomal membrane is a Pex3p-dependent process that does not require ATP/GTP hydrolysis. The system can be programmed with recombinant versions of Pex19p, allowing us to demonstrate that Pex19p-cargo protein complexes formed in the absence of peroxisomes are the substrates for the peroxisomal docking/insertion machinery. Data suggesting that cargo-loaded Pex19p displays a much higher affinity for Pex3p than Pex19p alone are also provided. These results suggest that soluble Pex19p participates in the targeting of newly synthesized peroxisomal membrane proteins to the organelle membrane and support the existence of a cargo-induced peroxisomal targeting mechanism for Pex19p.